COMPACT MULTIPURPOSE WORKING DESK DESIGN FOR NEURODIVERGENT GRAPHIC ARTISTS ON TAB SPACE - Faridah Awaloka Zahra; Didit Widiatmoko Suwardikun; Hanif Azhar; Yanuar Rahman (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The phenomenon of inclusive art for artists with disabilities, especially neurodivergent, has been gaining more attention in Indonesia. One of the art studios that supports neurodivergent artists is Tab Space, which provides a place and facilities for artists to work. However, until now, Tab Space has faced problems in providing adequate facilities, especially in terms of personal work areas for artists and also storage of large-scale works, given the limited space in the studio. This study uses a design thinking approach with the stages of empathize, define, ideate, prototype, and testing to design a solution that can overcome this problem. The results of this study are in the form of a proposal for a compact multipurpose working desk design that can provide a personal work area for neurodivergent artists, also provide a place to store large-scale works, while meeting functional needs and space efficiency. The benefits of this study are to provide design solutions that support the sustainability of neurodivergent artists' creativity, increase their comfort and productivity, and strengthen the inclusive arts ecosystem in Indonesia.